2014
DOI: 10.1016/j.neurobiolaging.2013.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Reduced excitatory amino acid transporter 1 and metabotropic glutamate receptor 5 expression in the cerebellum of fragile X mental retardation gene 1 premutation carriers with fragile X-associated tremor/ataxia syndrome

Abstract: A premutation (PM) expansion (55–200 CGG) in the fragile X mental retardation gene 1 (FMR1) causes elevated mRNA and reduced FMR1 protein (FMRP). Young PM carriers can develop characteristic physical features and mild cognitive disabilities. In addition, individuals with PM, particularly male carriers, are at high risk to develop Fragile X-associated tremor/ataxia syndrome (FXTAS) with aging. Human post-mortem FXTAS brains show extensive white matter disease in the cerebellum and the presence of intranuclear i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 60 publications
7
38
1
Order By: Relevance
“…The discrepancy between our results and those of other laboratories (Corti et al, 2011; Gupta et al, 2005; Matosin et al, 2013, 2014; Ohnuma et al, 2000; Pretto et al, 2014; Richardson-Burns et al, 2000; Volk et al, 2010) may reflect region-specific differences in mGluR5 expression (BA9 vs. BA10 vs. DLPFC vs. ACC vs. cerebellum); the different analytic techniques that were used (western blotting vs. receptor binding assays vs. qRT-PCR vs. immunocytochemistry); more importantly, the lack of measurement of monomer and dimer forms of mGluR5 in three studies (Corti et al, 2011; Gupta et al, 2005; Matosin et al, 2013) and the non-quantitative technique of measuring mGluR5 by immunocytochemistry in one study (Pretto et al, 2014); and lastly, differences between levels of mRNA and protein for mGluR5. The hypothesis that brain regional expression of mGluR5 may also account for differences between studies has recently been advocated by other laboratories (Matosin et al, 2014).…”
Section: Fmrp Regulon Impacts Expression Of Gaba Receptor Subunitscontrasting
confidence: 99%
See 2 more Smart Citations
“…The discrepancy between our results and those of other laboratories (Corti et al, 2011; Gupta et al, 2005; Matosin et al, 2013, 2014; Ohnuma et al, 2000; Pretto et al, 2014; Richardson-Burns et al, 2000; Volk et al, 2010) may reflect region-specific differences in mGluR5 expression (BA9 vs. BA10 vs. DLPFC vs. ACC vs. cerebellum); the different analytic techniques that were used (western blotting vs. receptor binding assays vs. qRT-PCR vs. immunocytochemistry); more importantly, the lack of measurement of monomer and dimer forms of mGluR5 in three studies (Corti et al, 2011; Gupta et al, 2005; Matosin et al, 2013) and the non-quantitative technique of measuring mGluR5 by immunocytochemistry in one study (Pretto et al, 2014); and lastly, differences between levels of mRNA and protein for mGluR5. The hypothesis that brain regional expression of mGluR5 may also account for differences between studies has recently been advocated by other laboratories (Matosin et al, 2014).…”
Section: Fmrp Regulon Impacts Expression Of Gaba Receptor Subunitscontrasting
confidence: 99%
“…Even in adults with autism, where mGluR5 levels were not significantly different than controls, ratios of mGluR5 to neuronal specific enolase (NSE) for both dimeric and total mGluR5 were increased by 96% in BA9 (Fatemi and Folsom, 2011; Fatemi et al, 2011a). In contrast, a recent article by Pretto et al (2014) demonstrated reduced expression of both FMRP and mGluR5 in cerebella of subjects with the FMR1 premutation who had been diagnosed with fragile X tremor/ataxia syndrome (FXTAS). The discrepancy between these findings and ours may be due to brain regional differences as we found non-significant reductions in mGluR5 in cerebellar vermis of adults with autism (Fatemi et al, 2011a).…”
Section: Fmrp Regulon Impacts Expression Of Gaba Receptor Subunitsmentioning
confidence: 91%
See 1 more Smart Citation
“…Patients have been described previously (Cases LR, 58-02-WD and 1007-05-HP from Greco et al., 2006 and Pretto et al., 2014). Fibroblasts of three FXTAS male individuals with confirmed pre-mutation of 84, 90, and 99 CGG repeats were obtained with the informed consent of individuals and approved by the Institutional Review Board of the Hospital La Pitié Salpêtrière.…”
Section: Methodsmentioning
confidence: 97%
“…However, as in unmethylated FXS patients, the repeat RNA forms a hairpin loop that impairs FMRP translation [5, 6]. This effect is repeat length dependent, such that larger CGG repeats elicit greater impairments in translational efficiency and lower FMRP levels [3, 7, 8]. Consistent with reduced FMRP levels, younger premutation carriers can develop symptoms more commonly associated with FXS, such as higher rates of autistic and attention deficit hyperactivity disorder (ADHD)-like symptoms [5, 9].…”
mentioning
confidence: 99%